A two-year long drought in summer 2014/2015 and 2015/2016 over South Africa - Monyela, Bellinda Mashoene (Department of Oceanography, 2018)
Droughts occurred over South Africa during the summer seasons of 2014/2015 and 2015/2016. At the same time, the Pacific Ocean was warmer than normal starting in 2014 and leading to the very strong 2015/2016 El Niño. The first objective of this study is to document the ocean and climate conditions that occurred during the summer seasons 2014/2015 and 2015/2016 in southern Africa. NCEP Reanalysis data is used to compute the monthly and seasonal scale composite mean and anomalies of large-scale circulations during the summer seasons of 2014/2015 and 2015/2016. Results obtained from the study suggest that some months of 2014/2015 and 2015/2016 were canonical to the effect of El Niño over southern Africa, but not all of them during the summer seasons were dry. The wetter than normal conditions in northeast South Africa, Botswana and Zimbabwe during December 2014 are unfamiliar for a canonical summer El Niño event over southern Africa. Anomalous cooler than normal Sea Surface Temperature (SST) occurred over the west coast and south coast during December 2014 and February 2015, while it is usually warmer during El Niño. Additionally, the colder than normal SST at the south coast during February 2016 and Namibian and West Coast during March 2016 does not mimic the canonical El Niño patterns. However, this did not influence the El Niño-like warmer seasonal SST average during 2015/2016. The lower than normal pressure anomalies over the subcontinent during December 2014 and January 2015 were not portraying a canonical El Niño pattern but the other months were. The seasonal larger than normal pressure at 500 hPa over the subcontinent was more typical of El Niño during summer 2015/2016 and acted to suppress rainfall. Secondly, the study uses the Standard Precipitation Index (SPI) at different time scales (3 months duration, 5 months duration and 17 months duration) to assess the severity of 2015/2016 summer drought compared to the other droughts of the 20th and 21st century (1921 to 2016) and to analyse the relationship between droughts and ENSO. The South African Weather Service (SAWS) rainfall data shows that KwaZulu-Natal was the only region within South Africa, to have the 2015/2016 as the strongest summer drought since 1921 but 2015/2016 was still one of the worst droughts on record in South Africa, especially at the 2 consecutive seasonal scales. In general, droughts are favored by El Niño and wetter conditions by La Niña, but the second strongest El Niño of 1997/1998 led to near normal rainfall over the north-eastern region at all time-scales. The SPI has proven to be very versatile, flexible and very effective to monitor the 2015/2016 summer drought in the complex South African rainfall regime. However, there was little difference between 3 months SPI at the end of February and 5 months SPI at the end of March. For South Africa, the summer rainfall 2015/2016 season had the fifth worst drought after El Niño related drought of 1982/1983 and 1991/1992 and the non-El Niño related droughts of 1967/1968 and 1944/1945. At the 17-month scale, an index that encompasses two summer seasons 2015/2016 was the third worst drought since summer 1921/1922 due to dry conditions in 2014/2015 and 2015/2016.